Understanding the costs of the Food Corporation of India - Swaminathan, Madhura (1999)
The debate on food subsidies in India affects millions of consumers and producers, and is of immense importance in a country in which chronic hunger and malnutrition affects a majority of the population. In this paper, I first examine the volume of the food subsidy over the last three decades. Secondly, using data for the 1990s from the accounts of the Food Corporation of India (FCI), I examine the components of the foodgrain subsidy, the relative contribution of different components to total costs, and the growth in different components during the current decade. Thirdly, I attempt to compare the efficiency of the FCI with that of private trade. The data from FCI performance budgets show clearly that the increase in procurement price was a critical factor in the increase in economic costs of rice and wheat. The procurement price, however, is a variable over which the FCI has no control as the central government sets the procurement price based on the recommendations of the Commission on Agricultural Costs and Prices. Despite the absolute increase in many components of costs, there was an improvement in the operational efficiency of the FCI during the 1990s. Lastly, no unambiguous finding emerged from a comparison of wholesale market prices and economic costs of the FCI. The FCI compared favourably with private traders in the distribution of rice in a large number of states. In the states of northern and central India, however, private traders had lower prices for grain. The presence of systematic rural-urban price differences indicated the imperfections of grain markets. - Reproduced
Keywords: Food Corporation of India